Long noncoding RNA MEG3 suppresses podocyte injury in diabetic nephropathy by inactivating Wnt/β-catenin signaling - Che,Xiajing; Deng,Xin; Xie,Kewei; Wang,Qin; Yan,Jiayi; Shao,Xinghua; Ni,Zhaohui; Ying,Liang (PeerJ, 2019)
Background Diabetic nephropathy (DN) is one of the principal complications of diabetes and podocyte injury plays an important role in the DN pathogenesis. Wnt/β-catenin signaling overactivation confers podocyte injury and promotes multiple types of renal disease. However, the underlying mechanism of Wnt/β-catenin signaling activation in DN progression has not been fully elucidated. Long noncoding RNA (lncRNA) is a large class of endogenous RNA molecules lacking functional code capacity and which participates in the pathogenesis of human disease, including DN. Method A diabetes model was constructed by intraperitoneal injection of Streptozotocin in rats. The MPC5 cells were used to create the in vitro model. Western blot and Quantitative reverse-transcriptase-PCR were used to examine the expression of protein and mRNA. The migrated capacity was analyzed by Transwell migration assay. The cell viability was detected by CCK8. Results In the present study, we revealed the association of lncRNA Maternally Expressed Gene 3 (MEG3) with aberrant activation of Wnt/β-catenin signaling and the role of MEG3/Wnt axis in podocyte injury. We found that high glucose (HG) treatment suppressed MEG3 expression in cultured podocytes, activated Wnt/β-catenin signaling and caused podocyte injury as indicated by the downregulation of podocyte-specific markers (podocin and synaptopodin) and the upregulation of snail1 and α-smooth muscle actin. Overexpression of MEG3 attenuated HG-induced podocyte injury by reducing Wnt/β-catenin activity, repressing cell migration, reactive oxygen species production and increasing the viability of podocytes. Furthermore, we provided evidences that restoration of Wnt/β-catenin signaling by specific agonist impeded the protective effect of MEG3 on podocyte injury. Current results demonstrated that MEG3/Wnt axis plays an important role in fostering podocyte injury and may serve as a potential therapeutic target for the treatment of DN. Conclusion lncRNA MEG3 ameliorates podocyte injury in DN via inactivating Wnt/β-catenin signaling.
Keywords: Podocytes injury; MEG3; Wnt/β-catenin; Diabetic nephropathy